1997
DOI: 10.1111/j.1365-246x.1997.tb00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Curie-temperature depth estimation using a self-similar magnetization model

Abstract: S U M M A R YThe Earth's crust is magnetized down to the Curie-temperature depth at about 10 to 50 km. This limited depth extent of the crustal magnetization is discernible in the power spectra of magnetic maps of South Africa and Central Asia. At short wavelengths, the power increases as rapidly towards longer wavelengths as expected for a self-similar magnetized crust with unlimited depth extent. Above wavelengths of about 100 km the power starts increasing less rapidly, indicating the absence of deep-seated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(136 citation statements)
references
References 35 publications
3
132
0
1
Order By: Relevance
“…The observed spectrum shows a fall-off in power at the longest wavelengths (> 20 km) compared to the synthetic values. This difference is often seen and is interpreted to be caused by the limited depth extent of magnetic sources (Maus et al, 1997;Bouligand et al, 2009). Using an FFT approach to compute the fractal field ensures the periodicity requirement at the extended grid edges is met.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed spectrum shows a fall-off in power at the longest wavelengths (> 20 km) compared to the synthetic values. This difference is often seen and is interpreted to be caused by the limited depth extent of magnetic sources (Maus et al, 1997;Bouligand et al, 2009). Using an FFT approach to compute the fractal field ensures the periodicity requirement at the extended grid edges is met.…”
Section: Methodsmentioning
confidence: 99%
“…For gravity data, published values of β range from −4.5 to −5 based on regional and continent-wide data compilations (Maus and Dimri, 1996;Maus et al, 1998;Pilkington and Todoeschuck, 2004). Magnetic data show a wide range of β values between −1 and −4.8, based on sample areas with scales from <10 km up to >1000 km (Gregotski et al, 1991;Pilkington and Todoeschuck, 1993;Maus and Dimri, 1995;1996;Maus et al, 1997;Bouligand et al, 2009). Although not a necessary requirement for the fractal (or scaling) potential field description (Fedi et al, 1997;Quarta et al, 2000), the spatial distribution of rock properties (density and magnetic susceptibility) that cause these fields are also fractal with behaviours summarized in Bouligand et al (2009).…”
Section: Fractal Description Of Potential Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited depth extent of the crustal magnetization would be visible in magnetic maps, covering less than 100 × 100 km (Maus et al 1997). Okubo et al (1985Okubo et al ( , 2003 suggested the optimal dimensions of the investigated square window to be about ten times the actual target depth (Hisarli et al 2011).…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…As a result of the large variability of magnetic field survey data and measured magnetic susceptibilities, several studies have applied fractal geometry techniques to magnetic field and susceptibility data models (Gettings et al, 1991;Gregotski et al, 1991;Todoeschuck, 1993, 1995;Pilkington et al, 1994;Maus and Dimri, 1994Maus et al, 1997;Zhou and Thybo, 1998;Maus, 1999;Quarta et al, 2000). Most authors (e.g.…”
Section: Basis For a Fractal Modelmentioning
confidence: 99%